KAJIAN EFISIENSI ENERGI DENGAN PENGATURAN SUPLAI ENERGI LISTRIK - Mochammad Mieftah (Politeknik Negeri Malang, 2018)
A power system can be said to be reliable if it has a high continuity of service. To achieve this, an operational arrangement is required to optimize installed power to supply the load to avoid overloading or over-supply of the system. Modjopanggoong Sugar Factory Tulungagung is one of the sugar producing industries, where the electrical system in this factory uses two power supply, which is using PLN supply and Turbine Generator Boiler (BTG). The use of more than one power supply resulted in an increase in the required electricity production costs. To solve this problem, in this research will be conducted a study to make efficient of electrical energy cost which is done by arranging supply of electric energy, that is using maximum supply of BTG and its deficiency supported PLN supply (alternative I), using PLN maximum supply and its deficiency is supported BTG supply alternative II) and only use PLN supply (alternative III). The results showed that energy efficiency can be done with the regulation of energy supply at the factory, that is in alternative I with savings Rp.430.025.007 (2.1%), alternative II with savings of Rp. 553,984,815 (2.7%), and alternative III with savings of Rp. 2.055.727.407 (10%).